How the relative permittivity of solar cell materials influences solar cell performance. (June 2017) - Crovetto, Andrea; Huss-Hansen, Mathias K.; Hansen, Ole
Highlights: A design rule for the permittivity of solar cell materials is proposed. Early-stage solar cell technologies become more robust by applying the design rule. High-permittivity materials are the best junction partners of novel solar absorbers. Abstract: The relative permittivity of the materials constituting heterojunction solar cells is usually not considered as a design parameter when searching for novel combinations of heterojunction materials. In this work, we investigate the validity of such an approach. Specifically, we show the effect of the materials permittivity on the physics and performance of the solar cell by means of numerical simulation supported by analytical relations. We demonstrate that, depending on the specific solar cell configuration and materials properties, there are scenarios where the relative permittivity has a major influence on the achievable conversion efficiency, and scenarios where its influence can be safely ignored. In particular, we argue that high-permittivity materials should always be the preferred choice as heterojunction partners of the absorber layer when prototyping new materials combinations. When the heterojunction partner has a high permittivity, solar cells are consistently more robust against several non-idealities that are especially likely to occur in early-stage development, when the device is not yet optimized.